Analisis Natrium Diklofenak Dalam Sampel Jamu Pegal Linu Yang Dijual Di Kabupaten Semarang Secara Klt-Spektrofotometri Uv-Vis - Padanun, Moudi Ayuty Viony; Tri Minarsih (Journal of Holistics and Health Science, 2021)
Herbal medicine for rheumatic pain is one of the traditional medicinal products that are massively demanded by the public because it has many benefits. Medicinal Chemicals (MC) are often added to herbal medicine for rheumatic pain to strengthen their properties, one of which is Diclofenac Sodium. Based on the Decree of the Minister of Health of the Republic of Indonesia No. 246 of 2010, traditional medicines are prohibited from containing Medicinal Chemicals (MC). This study aims to analyze the content of Diclofenac Sodium Medicinal Chemicals (MC) in the herbal medicine for rheumatic pain which is sold in Semarang Regency. This type of research was conducted using a laboratory experimental method which descriptively describes the results of the study based on the data obtained. The research method consisted of organoleptic test, qualitative analysis and quantitative analysis of the samples of herbal medicine for aches and pains. Organoleptic test was carried out by tasting the taste, smelling the smell, seeing the color and feeling the dosage form of the Jamu Pegal Linu sample. Qualitative analysis was performed by Thin Layer Chromatography (TLC) and quantitative analysis was performed by UV-Vis Spectrophotometry with 3 samples considered positive. Samples B, D, and E which is sold in Semarang Regency were positive for Diclofenac Sodium based on the Rf values ​​obtained from the samples, namely 0.28, 0.3, and 0.3, which were almost the same as the standard Rf for Sodium Diclofenac, which was 0.26. The stationary phase used a Silica Gel 254 and the mobile phase used Ethyl Acetate and N-Hexane in a ratio of 25: 25. In quantitative analysis, a wavelength of 275 nm was obtained with a linear equation y = 0.0245x + 0.0989 and a value of r = 0.9994 with a concentration of obtained in samples B, D, E were 39.27%, 2.67% and 4.9%, respectively. ABSTRAK Jamu Pegal Linu merupakan salah satu produk obat tradisional yang banyak diminati oleh masyarakat karena memiliki banyak manfaat. Bahan Kimia Obat (BKO) sering ditambahkan pada Jamu Pegal Linu untuk menambah khasiatnya, salah satunya adalah Natrium Diklofenak. Berdasarkan Permenkes RI No. 246 tahun 2010, obat tradisional dilarang mengandung BKO. Penelitian ini bertujuan untuk menganalisis kandungan Natrium Diklofenak pada sediaan Jamu Pegal Linu yang dijual di Kabupaten Semarang. Jenis penelitian dilakukan menggunakan metode eksperimental laboratorium. Metode penelitian terdiri dari uji organoleptis, analisis kualitatif dan kuantitatif. Uji organoleptis dilakukan dengan dengan cara mengamati warna, bau, rasa dan bentuk sampel. Analisis kualitatif dilakukan dengan Kromatografi Lapis Tipis (KLT) dan analisis kuantitatif dilakukan dengan Spektrofotometri UV-Vis. Sampel B, D, dan E yang dijual di Kabupaten Semarang positif mengandung Natrium Diklofenak berdasarkan nilai Rf yang didapatkan dari sampel berturut-turut yaitu 0.28, 0.3, dan 0.3 mendekati nilai Rf baku Natrium Diklfenak yaitu 0.26. Fase diam menggunakan Silica Gel 254 dan fase gerak menggunakan Etil Asetat dan N-Heksan dengan perbandingan 25 : 25. Pada analisis kuantitatif diperoleh panjang gelombang 275 nm dengan persamaan garis linier y = 0,0245x + 0,0989 dan nilai r = 0.9994 dengan kadar pada sampel B, D, E berturut-turut adalah 39.27%, 2.67% dan 4.9%.